Pemanfaatan Vinasse sebagai Pupuk Organik Cair untuk Meningkatkan Pertumbuhan dan Hasil Bunga Kol (Brassica oleracea var. Botrytis L.) - Siti Ma'rufah; Riza Yuli Rusdiana; Vega kartika sari (Jurnal Penelitian Pertanian Terapan, 2020)
Cauliflower is a annual vegetable crop that is rich in vitamins and minerals. Â This is one of the commodities exported by Indonesia. Fertilization is a determinant of the success of vegetable farming. The use of chemical fertilizers that are not balanced with organic fertilizers can have a negative impact on the environment. Vinasse is an industrial waste that is rich in organic matter, potassium, calcium and micro nutrients and can be used as liquid organic fertilizer. This study aims to determine the effect of giving several doses of vinasse on the growth and production of cauliflower. The experimental design used is a single factor Randomized Block Design (RCBD). The treatment dose used consisted of four levels namely, 0 l / ha (V0), 15000 l / ha (V1), 20000 l / ha (V2), 25000 l / ha (V3). The results showed that there was a very significant effect on plant height at 14 DAP and 21 DAP, and on the variabels of flower weight per sample, flower weight per bed, and fresh stover weight per sample, and showed a significant effect on the number of leafÂ  variabel on age 14 DAP and 21 DAP. The best treatment of vinasse fertilizer is 25000 l / ha (V3).